2017
DOI: 10.1038/s41598-017-18066-7
|View full text |Cite
|
Sign up to set email alerts
|

The kinematics of handwriting movements as expression of cognitive and sensorimotor impairments in people with multiple sclerosis

Abstract: Handwriting is an important activity of daily living, which requires sensorimotor and cognitive skills that could deteriorate in presence of neurological diseases. Handwriting impairments are common in people with multiple sclerosis (PwMS). Aims of the present study were to characterize handwriting movement features of PwMS in comparison with those of healthy adults, and to evaluate the relationship between kinematic parameters of handwriting movements and the results of the assessment of cognitive and motor d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 77 publications
1
10
0
Order By: Relevance
“… Schenk et al (2000) found that, although the script of PwMS, compared with healthy subjects, was still legible, the writing speed decreased and stroke duration increased ( Schenk et al, 2000 ). In line with this study, we recently showed that handwriting movements of PwMS significantly differed from those of healthy controls (HC) in the time spent to write a sentence, which was due to increased duration of the words and the spacing between words ( Bisio et al, 2017 ).…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“… Schenk et al (2000) found that, although the script of PwMS, compared with healthy subjects, was still legible, the writing speed decreased and stroke duration increased ( Schenk et al, 2000 ). In line with this study, we recently showed that handwriting movements of PwMS significantly differed from those of healthy controls (HC) in the time spent to write a sentence, which was due to increased duration of the words and the spacing between words ( Bisio et al, 2017 ).…”
Section: Introductionsupporting
confidence: 75%
“…In this context, it should be considered that functional decline among PwMS embraces worsening of handwriting ( Rosenblum and Tamar Weiss, 2010 ). Indeed, handwriting deficits are common in multiple sclerosis, but studies on this aspect of the disease are rare ( Wellingham-Jones, 1991 ; Schenk et al, 2000 ; Bisio et al, 2017 ). In particular, PwMS show handwriting impairments that are mainly referred to the temporal features of the task.…”
Section: Introductionmentioning
confidence: 99%
“…In this line of research, studies differ in the specific measures employed. Some authors have used kinematic writing measures such as velocity, acceleration, average normalized jerk [ 39 ] or fluency [ 36 , 40 42 ]. Further, pressure or in air-time measures, have also been used in the evaluation of motor symptoms [ 35 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this framework, it is clear that a technology that allows the combined study of handwriting and tremor features perfectly suits the current needs of the neurological research field. Indeed, the importance of studying handwriting is not restricted to Parkinson's Disease, but can be extended to a variety of other neurological disorders, including Dyskinesia [44], Huntington's Disease [4], and Multiple Sclerosis [45], not only to support the diagnosis process, but also to quantify the severity of clinical signs over time and to monitor and manage the risks associated with medications [44]. In addition, a technology that allows quantitative, simple, and ecologically valid evaluation of handwriting finds potential and interesting applications also in the youngest population, since handwriting and text production skills assume a central role in the children's development process.…”
Section: Discussionmentioning
confidence: 99%